The CAF Assessment Framework for Quality Measurment in Public Administration - Dončev, Aleksandar; Jereb, Eva (Organizacija in organiziranje, 2025)
The chapter focuses on explaining the introduction of the Common Assessment Framework (CAF) for quality measurements in public administration. It describes the changes that began to take place under the influence of globalization and the opening of Slovenia to the world, as well as the adaptation of public bodies and institutions to new ways of measuring quality. Quality measurement results are crucial to improving operations and achieving high-quality standards in public administration. The importance of introducing quality measurement based on the existing standard of the European Foundation for Quality Measurement EFQM is presented, as it served as the basis for creating the CAF evaluation framework. In addition to the introduction of the CAF, the idea of introducing other existing standards that ensure more significant order and greater transparency in the operation of public administration continues to be encouraged.